Monitoring Patient Based-Home - Abbas, Hussain Laith; Abd, Taher Falah; Talib, Taha qusay; kadhim, Mustafa Hadi; Habeeb, Dr. Zeyad Qasim (Journal of Science in Medicine and Life, 2025)
Remote patient monitoring (RPM) is a form of telehealth, or healthcare delivered remotely. The popularity of telemedicine has been on the rise since the outbreak of the pandemic, it brings in new models of care along remote patient monitoring (RPM) of key health metrics to improve chronic care management next decade will see an impressive increase in remote patient monitoring (RPM) devices, at a growth rate of 12.5 percent annually. The trend is quite predictable considering the cumulative effects of the aging population, the high cost of in-patient care, and enormous pressure on hospitals caused by COVID-19.